If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -4 = 90 Reorder the terms: -4 + 2p = 90 Solving -4 + 2p = 90 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2p = 90 + 4 Combine like terms: -4 + 4 = 0 0 + 2p = 90 + 4 2p = 90 + 4 Combine like terms: 90 + 4 = 94 2p = 94 Divide each side by '2'. p = 47 Simplifying p = 47
| 15-6x-2y=4 | | 1/2(48=40)35 | | 42-(3c+4)=2(c+4)+6 | | 30+6y=12+6w | | -p+12=8 | | 1/2(48=40 | | 14=2(2n-1) | | 0.5x+12=46 | | .8s=24 | | 4x-11=x+55 | | 6-3+4x+1=1x+4 | | 57-x=41 | | .75e=15 | | 26=3y-17 | | 6-3+4x+1=1x+5 | | 10=2y-17 | | 3x+200=4x | | 19x+7y=-13 | | 10=2y-16 | | 1+7x=7x+1 | | 61+3a+90=180 | | 10=(n+2) | | -9y+10=10y | | 3k-32=12 | | 2x+6=4x+(-2) | | 5/7•2/9 | | 5+20x-16x^2=0 | | x+4(22-7y)=14 | | .75d=46.50 | | x+4(22-7y)=15 | | 5(x-7)-9=-5(-5x+6)-4x | | 26=3y+16 |